The Development of Assessment Guidelines for Patients with Acute Coronary Syndrome. - Mali, Panumart; Chainan, Kannika; Sangduang, Niphitpon (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2024)
The objective of this research and development were 1) to develop guidelines for assessment patients with acute coronary syndrome, and 2) to study the effectiveness of guidelines for assessment patients with acute coronary syndrome. The sample group consists of patients exhibiting symptoms of acute coronary syndrome. The data collection tools include: guidelines for assessment patients with acute coronary syndrome, questionnaires for the comments regarding the assessment guidelines for patients, and satisfaction surveys. The quality of the tools is examined through content validity checks and reliability assessments. Data is analyzed using descriptive and paired t-test. The results showed that: 1) the developed assessment guidelines for patients form includes evaluations of the patient's initial condition, key symptoms, associated symptoms, significant risk factors, time of arrival at the emergency room, time of electrocardiogram examination, interpretation of test results, and physician diagnosis, 2) the comments regarding the assessment guidelines for patients form had high levels ( = 4.38, SD = 0.76), 3) the sample group that used the patient assessment form showed a high level of satisfaction with the assessment, ( = 4.28, SD = 0.73). The average time for accessing electrocardiogram examinations significantly differs between the group of patients with acute coronary syndrome who use the patient assessment form and those who do not, with statistical significance at the 0.05 level (t = 3.10). The group used the assessment form has a shorter average access time to electrocardiogram examinations compared to the group not using the assessment form. This suggests that the developed guidelines for assessment patients to be screened, assessment, differential diagnosis and able to access essential treatment in a time. As a result, the death rate decreased.